Effect of animal glue on mineralogy, strength and weathering resistance of calcium sulfate-based composite materials. (February 2019) - Elert, Kerstin; Benavides-Reyes, Cristina; Cardell, Carolina
Abstract: Calcium sulfate (gypsum, bassanite, and anhydrite) has been widely used since ancient times as decorative plaster and painting grounds, often mixed with organic additives (e.g., animal glue). In order to evaluate the effect of organic additives on gypsum setting and on the product's final properties, calcium sulfate-based plaster samples, with and without the addition of animal glue, were subjected to accelerated weathering and mechanical testing. Test results were related to the samples' mineralogical composition. Animal glue improved mechanical properties and weathering resistance, but retarded gypsum setting and resulted in long-term stabilization of metastable bassanite and anhydrite. Accelerated weathering (wetting/drying cycles) resulted in changes in mineral phases and micro-texture, affecting mechanical properties and facilitating deterioration due to phase transition-related volume changes. Findings are discussed with respect to applications of calcium sulfate-based materials in conservation and rehabilitation interventions.